Virtual screening of naphthoquinone analogs for potent inhibitors against the cancer‐signaling PI3K/AKT/mTOR pathway. Issue 2 (8th October 2018) - Rehan, Mohd; Bajouh, Osama S.
Abstract: The PI3K/AKT/mTOR pathway is one of the most commonly disrupted signaling pathways that plays a role in the development and pathogenicity of multiple cancers. Therefore, the critical proteins of this pathway have been targeted for anticancer therapy. The scientific community has increasingly been realizing the anti‐cancer therapeutic potential of naphthoquinone analogs. These compounds constitute a major class of diverse sets of plant metabolites, which include various natural products and synthetic compounds with proven anticancer activity. The current study involved structural computational biology approaches to explore compounds from a diverse pool of naphthoquinone analogs that can inhibit key cancer‐signaling proteins phosphoinositide 3‐kinase (PI3K), protein kinase B, PKB (AKT), and mammalian target of rapamycin (mTOR). The novel compound identified commonly among the top 10 dock score lists of PI3K, AKT, and mTOR was selected for further study and proposed as a potential inhibitor of the 3 cancer‐signaling proteins and an anticancer agent. Further, to check the docking accuracy and potential of the compound, post docking analyses, namely, binding comparison with the native ligand, the role of the interacting residue role in binding, predicted binding energy and dissociation constant calculations, etc., were performed. All these measures showed good‐quality binding, and thus provide weight to our prediction of the novel compound as a pan PI3K/AKT/mTOR inhibitor and an anticancer agent. Finally, to compare the binding and similarity in the active sites of the 3 protein kinases, a ligand‐based active site alignment was performed and analyzed. Thus, the study proposed a novel naphthoquinone analog as a potential anticancer drug, and provided comparative structural insight into its binding to the 3 protein kinases. Abstract : A novel naphthoquinone compound with PubChem CID, 20759629, obtained through virtual screening is proposed as a pan PI3K‐AKT‐mammalian target of rapamycin (mTOR) inhibitor and an anticancer agent. Comparative analyses of active sites with respect to the bound proposed inhibitor revealed the equivalent residues found to be identical or similar in physicochemical properties.